The cooking therapy for cognitive rehabilitation of cerebellar damage: A case report and a review of the literature. (January 2019) - Cerasa, Antonio; Arcuri, Francesco; Pignataro, Luigina Maria; Serra, Sebastiano; Messina, Demetrio; Carozzo, Simone; Biafora, Antonio; Ceraudo, Caterina; Abbruzzino, Luca; Pignolo, Loris; Basta, Giuseppina; Tonin, Paolo
Graphical abstract: The cooking therapy framework for the rehabilitation of the cerebellar patients. The patient underwent 18 levels divided into three courses (starter, pasta, and main) X 2 food meals (meat-fish) X 3 levels of difficulty (1°–2°–3° meal). Tomato sauce is the main food, which is prepared each time for every single meal. All cooking levels started with the preparation of this food. Task difficulty varied as a function of the number of foods (motor sequence) and timing. The factor "timing" means the number of foods to be cooked simultaneously, whilst the factor "sequencing" indicates the increasing number of motor sequences to be performed and learned. Red dot lines represent the number of motor sequences, which are executed during the three levels. Highlights: Rehabilitation approach for cerebellar patients are sparsely documented. Cerebellar damages induced executive dysfunctions. Cooking therapy has been demonstrated to stimulate multitasking activities. Cooking therapy increases executive functions in cerebellar patient. Approach where patient is aware of its deficit is preferred. Abstract: Background and importance: The therapeutic approach for cerebellar damages heavily relies on neurorehabilitation since there are no medications that may improve clinical symptoms mainly those related to cognitive dysfunctions. Nevertheless, neurorehabilitation programs tailored to cerebellar damages have never been validated. Here we describe a new rehabilitation approach based on cooking training (CT). The idea that cooking may stimulate cerebellar activity relies on previous evidence demonstrating the beneficial effect on the executive functions as well as in promoting neural plasticity within the cerebellum. Indeed, CT requires motor/mental coordination, thinking flexibly, planning, implementing strategies, shifting and self-monitoring behaviors, all functions drastically affected in cerebellar disorders. Case description: A 68-year-old male stroke patient with isolated right cerebellar ischemia in the posterior cerebellum characterized by mild executive dysfunctions. After intensive six weekly two-hour sessions, we found that CT was effective in improving some cognitive abilities in a context of mild motor impairment. In particular, deficits in the execution of the Symbol digit modality test and Wisconsin card-sorting test were recovered. Conclusion: The comparison of our data with those reported in previous studies confirmed the Schmahmann's hypothesis on the effectiveness of neurorehabilitation approaches in cerebellar patients acting as external timekeeping of conscious thoughts.